"Taking Back Our Country": Tea Party Membership and Support for Punitive Crime Control Policies. Issue 2 (14th March 2014) - Pickett, Justin T.; Tope, Daniel; Bellandi, Rose
<x xml:space="preserve">Abstract</x> The Tea Party Movement (TPM) emerged shortly after the 2008 election, with members rallying behind the call to "take back our country." Many observers suggest that the movement represents, in part, a racialized backlash against the election of Barack Obama, the nation's first black president, motivated by perceived threats to the racial hierarchy. Racial threat theory predicts that if the TPM is motivated by and reinforces racial concerns, racialized support for punitive crime policies that disproportionately impact blacks should be higher among Tea Partiers. Drawing on recent national survey data, this study tests this prediction. The results show that TPM membership is positively associated with punitiveness and that this relationship is mediated, in part, by Tea Partiers' animus toward blacks. We discuss the import of these findings for competing accounts of the TPM, racial threat theory, and the argument that the United States has become a "post‐racial society."